2020
DOI: 10.1063/1.5127315
|View full text |Cite
|
Sign up to set email alerts
|

Upper hybrid resonance heating experiments by X-mode microwaves on electron cyclotron resonance ion source

Abstract: We have considered the accessibility condition of electromagnetic and electrostatic waves propagating in an electron cyclotron resonance (ECR) ion source (ECRIS) plasma and then investigated experimentally their correspondence relationships with production of multicharged ions. It has been clarified that there exists an efficient configuration of ECR zones for producing multicharged ion beams and has been suggested that a new resonance, i.e., upper hybrid resonance (UHR), must have occurred. We have been tryin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Since it is difficult to distinguish the phenomenon of ECR and UHR with ordinary single frequency microwaves, we introduced microwaves for ECR and at the same time introduced high frequency microwaves far from that frequency in X-mode. As a result, we observed an increase in multicharged ion currents due to the UHR and simultaneously an increase on the high energy side of electron energy distribution function that supported it [10]. Furthermore, Dual ECR experiment was conducted and the yield of multicharged ions was successfully increased [11].…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…Since it is difficult to distinguish the phenomenon of ECR and UHR with ordinary single frequency microwaves, we introduced microwaves for ECR and at the same time introduced high frequency microwaves far from that frequency in X-mode. As a result, we observed an increase in multicharged ion currents due to the UHR and simultaneously an increase on the high energy side of electron energy distribution function that supported it [10]. Furthermore, Dual ECR experiment was conducted and the yield of multicharged ions was successfully increased [11].…”
Section: Introductionmentioning
confidence: 68%
“…As a result, it was shown that the multicharged ion current is usually saturated with each single microwave power supply, but the increased multicharged ion currents can be obtained by simultaneous power supply [11]. Kato et al, the same group conducted an UHR experiment with X-mode pioneeringly on 2.45GHz ECRIS superimposed by using 4-6GHz microwaves [10].…”
Section: Other Candidates For Furthermore Improvements Of Multicharge...mentioning
confidence: 99%
“…We focus on the gas mixing effect [2] [3], which is known as an empirical method to increase multicharged ions in ECRIS's. In our previous studies, the increase of Ar multicharged ion yield has been confirmed by the upper hybrid resonance (UHR) [4] using 4-6 GHz Xmode microwaves, the dual ECR heating method [5] in which microwaves are fed from two antennas simultaneously. We are attempting to increase the multicharged ions using lower hybrid resonance (LHR) by introducing low frequency electromagnetic waves (radio frequency waves: RF waves).…”
Section: Introductionmentioning
confidence: 84%
“…In the highfrequency EM waves, one method is to induce resonance by mode conversion from EM waves with various cutoff densities, etc., to electrostatic waves with no cutoff densities. Results have already been obtained in upper hybrid resonance (UHR) experiments [7] independently supplying microwave powers from both upstream and downstream of the ECR zone [8]. On the other hand, in high-density regions, resonance phenomena using low-frequency EM waves (usually called Radio Frequency: RF) are known as lower hybrid resonance (LHR) and ion cyclotron resonance (ICR).…”
Section: Introductionmentioning
confidence: 99%